Pengembangan Kelompok Sadar Wisata (POKDARWIS) Kawasan Karst - Tohani, Entoh; Wibawa, Lutfi; Prasetyo, Iis (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2018)
The reported community development program aimed at increase the ability of tourism awareness group in managing the karts area tourism area; and build group awareness to exploit karst region tourism potential. This activity was held for 24 people involved in tourism awereness group namely the "Mudal Wisata" group located in Gebangharjo, Pracimantoro, Wonogiri. It used  education and training which is includes stages: planning, implementation, and evaluation using adult-learning and experience-based approaches. The program have brought advantages in term of the target group able to increase awareness to utilize all potentials in karst area, possessing attitude, knowledge and skills of the target group in managing karst tourism service area, able to recognize the tourism potential that can be developed, and able to see innovatif program development efforts in the karst area. Nevertheless, unfortunately result of activities in the form of awake tourism groups that are able to make an effective and superior tourism program can not be achieved because of, in addition to technical factors, differences of interests exist between group members and group administrators. Therefore, another development action is needed that enables the target group to apply the attitudes, skills and knowledge possessed in the tourism implementation activities.